2016
DOI: 10.2399/ana.15.020
|View full text |Cite
|
Sign up to set email alerts
|

Radiological assessment of age from epiphyseal fusion at the knee joint

Abstract: Objectives: Age determination is needed in administration of justice, employment, marriage, forensic investigation and identification. This cross-sectional study aimed to investigate the relationship between stages of epiphyseal union at the knee joint and chronological age. Methods:Anterior posterior and lateral knee radiographs of 100 males and 110 females aged 9-19 years were examined. Epiphyseal union was divided into five specific stages in the femur, tibia and fibula. Fusion was scored as stage 0: non-un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…According to statistical results, the vast majority of cases were in the age group of more than 18 years and the reason for this is that this age group is more in need of citizenship or civil status ID for work, travel, and marriage. This finding agrees with a study done previously [5].…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…According to statistical results, the vast majority of cases were in the age group of more than 18 years and the reason for this is that this age group is more in need of citizenship or civil status ID for work, travel, and marriage. This finding agrees with a study done previously [5].…”
Section: Resultssupporting
confidence: 94%
“…Oladunni, Dennis, Nwabneze, and Steplea Onyia, India (2015), studied 100 males and 110 females, the number of stages was 5 by plain Xray, the finding in their study suggested that the radiographic analysis of the knee was a valuable alternative for estimation of chronological age [5].…”
Section: рентгенологическая оценка возраста по закрытию эпифизарной з...mentioning
confidence: 99%
“…The value of teeth in assessing individual age is widely accepted in forensic sciences and numerous areas of human life, such as socioeconomic, legal aspects, and dental treatment planning (Koshy and Tandon 1998;Franco et al 2013). Several studies have been performed on the estimation of human biological age (Cameriere et al 2004); most of those are focused on skeletal markers (Priya 2017) such as epiphyseal and cranial suture fusions (Ebeye et al 2016), hand-wrist bones (Benjavongkulchai and Pittayapat 2018), sternoclavicular bones (Ufuk et al 2016), and dental maturation (Manjunatha and Soni 2014).…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Many studies in forensic fields deal with the estimation of biological age in humans have been developed. 9 The most common methods rely on skeletal indicators 10 such as epiphyseal fusion, 11 hand-wrist bones, 12 sternoclavicular bones, 13 cranial sutures fusion and dental maturation. 14 According to the previous study, the radiograph of the hand-wrist and dental development is the most reliable method for assessing the biological age of children and juveniles.…”
Section: Introductionmentioning
confidence: 99%